2016
DOI: 10.1071/py14067
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lankan-born women who have given birth in Victoria: a survey of their primary postpartum health-care needs

Abstract: Women who migrate are vulnerable after giving birth. Normal postpartum adaptive challenges are heightened by separation from family and lack of familiarity with local services. The aim was to investigate primary care needs among Sri Lankan-born women with at least one Victorian-born child aged under 2 years. Health care, information and support needs and unmet needs were assessed in a structured Sinhala or English survey offered in print, online or by telephone. Fifty women provided data. Most (80%) had at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…There was a trend (nonsignificant) for parents born outside Australia to be more likely than Australian-born parents to seek information on the internet related to child feeding (mothers) or child health (fathers). This is in line with 2 qualitative studies that showed that barriers related to language, cultural beliefs, and unfamiliarity with health services drive immigrants to seek postnatal health information primarily from their personal network and the internet [35,36]. Further research is required to understand how ethnic minority groups seek information relevant to family lifestyle behaviors and to better understand the potential for Web-based resources in reaching these parents.…”
Section: Discussionsupporting
confidence: 63%
“…There was a trend (nonsignificant) for parents born outside Australia to be more likely than Australian-born parents to seek information on the internet related to child feeding (mothers) or child health (fathers). This is in line with 2 qualitative studies that showed that barriers related to language, cultural beliefs, and unfamiliarity with health services drive immigrants to seek postnatal health information primarily from their personal network and the internet [35,36]. Further research is required to understand how ethnic minority groups seek information relevant to family lifestyle behaviors and to better understand the potential for Web-based resources in reaching these parents.…”
Section: Discussionsupporting
confidence: 63%
“…There was a general consensus that women experienced an increased reliance on their partner for support during the perinatal period after migration [ 38 , 39 ]. Qualitative research suggests this was primarily because they lacked support from extended family and community that they would have experienced in their home country [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%